Pandangan Gen Z Dalam Membentuk Co-Creation: Sebuah Gambaran Kecil Melalui Kajian Pustaka Coffee Shop - Hafidz Hanafiah; Irwan Sukmawan; Irma Nurmala Dewi (Jurnal Kewirausahaan Cerdas dan Digital, 2024)
Generation Z has unique characteristics compared to other generations. A generation that is always looking for references for something almost 24 hours a day via mobile technology and social networks. The aim of this research is to determine Generation Z's opinions on forming co-creation in coffee shop properties that are currently trending. In addition to the development of digital marketing and the growth of coffee shop businesses in Indonesia, this generation is used to giving feedback and suggestions via social media or directly.The research method used utilizes literature studies and literature reviews from books, journals and previous consultancy research institutions. The results of the research show that Generation Z plays a role and actively participates in the formation of co-creation in coffee shops, although Zero Consumers are said to be among those who do not care about the menu, price, quality, etc. hold. Brand, The atmosphere in the cafeteria.